The Political Influence of Environmental Law in Indonesia - Muhammad Nur Fadilah Syahraya (Proceeding International Conference Restructuring and Transforming Law, 2024)
Man is only dependent on nature, because it is nature that is powerful. Nature will do as man does to him. Therefore, man himself is the one who makes regulations about nature in the hope that it will be a limit to human behavior against nature. But the greed of man who can fight anything that prevents him from making this regulation is only limited to writing and sanctions only limited to formalities. Time and time again our eyes have proven that humans are indeed truly greedy. Allah should have created man as a caliph, not as a destroyer. God created this earth to meet human needs, not greed. This study will review a little about the increasingly narrow role of environmental law in Indonesia by providing juridical-normative exposure by looking directly at the data in the field.